(untitled) (Veterinary Science, 2024)
In recent years, the use of alternative strategies to reduce the meat microbial load has been explored, among them the application of UV-C radiation and essential oils, seeking not to affect its sensory quality. In this study, the effect of the application of rosemary essential oil (REO) (5 %) and UV-C light (dose: 0,56 J/cm2) individually and combined on the colour stability of beef (Longissimus dorsi muscle) was studied. Four groups of samples were used: treated with UV-C light (I), with REO/lactic acid solution (R), with both treatments (I+R) and without treatment (C).Samples were stored at 0, 4 and 8 °C for 20, 14 and 8 days, respectively. To monitor surface colour changes, the parameters lightness (L*), redness (a*) and yellowness (b*) were obtained using a computer vision system and the total colour change (ΔE) was calculated. L* did not show significant changes (p>0,05) in any of the situations studied, with the a* coordinate being the one that best represented the observed changes. The greatest decrease in this parameter was observed in samples (C) and (I), while the application of REO allowed the a* value to be maintained without significant variations. Regarding ΔE, it presented a similar trend to a*, showing the capacity to delay the oxidation of the REO/lactic acid solution. In conclusion, theapplication of UV-C light together with the REO/lactic acid solution would delay the deterioration of the surface colour of fresh meat during refrigerated storage